Problem-Based Learning Guidelines for Optimizing Science Process Skills - Novia Ayu Sekar Pertiwi; Siti Sukowati Wanafaktu Miruki; Ino Angga Putra; Kartika Wulandari (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Teachers should be able to stimulate students' science process skills or be able to stimulate students' creativity. This study aims to develop a practical work guideline for Basic Electronics I based on Problem-Based Learning (PBL) designed to improve the science process skills of physics education students. This study uses a 4D development model, but is limited to the Develop stage, with a focus on a systematic planning process and the development of valid and practical teaching materials. The research data consists of expert validation and student responses regarding the practicality of the developed product. The instruments used were an expert validation sheet and a student response questionnaire, both using a Likert scale of 1–4. Data were analyzed quantitatively by calculating the average score and percentage, then broken down into levels of validity and practicality. The results showed that the practical guidelines were assessed as “very valid” by material experts (85%) and media experts (86%). Student responses to the practicality questionnaire also showed “very practical” with a score of 88.7% and a positive response of 81.3%. These findings indicate that the PBL-based Basic Electronics I practicum guidelines, which include Kirchhoff's Current Law, Ohm's Law, and voltage dividers, are valid and practical, making them suitable for use as alternative teaching materials to support practicum activities and optimize students' science process skills. Further researchers are advised to add learning outcome evaluation instruments to determine the direct impact of PBL-based practicum guidelines on students' conceptual mastery and critical thinking skills.